APPLICATION OF AUTHENTIC ASSESSMENT IN IMPROVING STUDENTS' SPEAKING SKILLS IN THE RELIGIOUS PROGRAM (MANPK) ISLAMIC STATE SENIOR HIGH SCHOOL 1 JEMBER - Zainal Islam, Muhammad Rizqi; Maulana, Bayu Wahyu; Rosyidi, Abdul Wahab; Anam, Syamsul (Abjadia : International Journal of Education, 2024)
This This research was conducted with the aim of finding out the implementation of authentic assessment in increasing the Maharah Kalam of Madrasah Aliyah Religious Program (MANPK) Students islamic state senior high school 1 jember. This research uses descriptive qualitative, while the data collection techniques use interviews, observation, documentation, while the techniques used in this research use data validity techniques which are carried out by triangulating sources and techniques. interaction analysis with steps of data collection, data reduction, data presentation and drawing conclusions or verification. From the results of this research, there are three assessments, namely knowledge, namely the teacher uses written test instruments and oral tests. The oral test is carried out at Maharah Kalam, while the written test is carried out after one lesson or at the end of the semester. The attitude assessment carried out in the MANPK program is seen from the aspect of student discipline both in class and in the dormitory. The assessment of Arabic language learning skills at Maharah Kalam is direct practice during the teaching and learning process in class using the books Al-'Arabiyah Lil Hayah and Al-'Arabiyah Baina Yadaik.